2019
DOI: 10.1111/sji.12830
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐associated B cells in urothelial urinary bladder cancer

Abstract: Tumour infiltrating B cells and CD38 + plasma cells have been correlated with survival in different malignancies but their role in urinary bladder cancer is unclear. IL-10 is a multifunctional cytokine with both anti-inflammatory and immunostimulatory properties, that can be released by regulatory B cells (Bregs). We have stained paraffin-embedded tumour sections from 31 patients with invasive urothelial urinary bladder cancer with respect to CD20 + B cells, CD38 + cells, IL-10-expressing cells, IgG, C1q and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Interestingly, in this high IgG and C1q positive tumors, almost 40% also present membranous staining with an anti-C3a detecting antibody. This study suggests the possibility that the activation of the classical pathway could be favorable for the patient's survival [35]. However, recent studies revealed that in lung and renal cancers the activation of the classical pathway by intratumoral immunoglobulins is associated with poor prognosis [23,34].…”
Section: Activation Of Complement In the Tumor Microenvironmentmentioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, in this high IgG and C1q positive tumors, almost 40% also present membranous staining with an anti-C3a detecting antibody. This study suggests the possibility that the activation of the classical pathway could be favorable for the patient's survival [35]. However, recent studies revealed that in lung and renal cancers the activation of the classical pathway by intratumoral immunoglobulins is associated with poor prognosis [23,34].…”
Section: Activation Of Complement In the Tumor Microenvironmentmentioning
confidence: 74%
“…In non-small cell lung cancer (NSCLC), IgM deposits are observed, pointing to a potential binding of the IgM to the neoantigens present at the tumor cell surface and a triggering of the classical pathway activation [34]. Furthermore, in human urothelial urinary bladder cancer, 50% of tumors with high levels of IgG antibodies also display C1q [35]. Interestingly, in this high IgG and C1q positive tumors, almost 40% also present membranous staining with an anti-C3a detecting antibody.…”
Section: Activation Of Complement In the Tumor Microenvironmentmentioning
confidence: 99%
“…B cell is a prognostic factor in many cancers (such as high grade serous ovarian cancer) [ 44 ]. CD20 B cells have also been reported to be associated with longer survival in bladder cancer [ 45 ]. Bladder cancer has a certain response to immunotherapy, but there is a lack of unique immune prognostic biomarker to guide treatment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidans play significant roles in mutation of dendritic cells, activity of T and B lymphocytes, macrophages, and natural killer cells, and differentiation of macrophages in different experimental models, including cancer xenograft models [12,99,[108][109][110]. Importantly, such an immune system is closely associated with malignant potential and outcome of BC cells [111][112][113][114]. Additionally, immune therapy is currently recognized as a major treatment in patients with BC [115,116].…”
Section: Future Directionsmentioning
confidence: 99%